Quality of dried rice noodles incorporated with differently encapsulated carrot powders - Ismail, H.; Karim, R.; Syed Muhammad, Sharifah Kharidah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Carrot powders which were differently encapsulated using wall materials such as maltodextrin DE10 (MD), resistant maltodextrin (RMD), CAPSUL® (CAP) and HI-CAP® 100 (HP) were incorporated into extruded rice noodles. Each carrot powder at three different levels (5-15 %) was mixed with rice flour and tapioca starch blend (80:20) and the moisture content of the feed was adjusted to 30 % before extrusion at 80 °C, 100 °C, 100 °C, 100 °C for zones 1, 2, 3 and 4 of the extruder barrel, respectively, with a feed rate of 20 rpm and screw speed of 60 rpm. The noodles were dried at 30 °C for 16 hours and then evaluated for retention of ß-carotene, colour, cooking quality and textural properties. The level of carrot powder used and the type of wall material have an effect on the quality of the noodles. ß-carotene from carrot powders spray dried with HP was retained the highest in the noodles followed by that from carrot powders encapsulated with MD, CAP and RMD. Rice noodles incorporated with HP and CAP encapsulated carrot powders were more orange in colour compared to noodles containing MD and RMD encapsulated carrot powders. Rice noodle containing 15 % RMD encapsulated carrot powder showed the highest rehydration (213.40 %) and the lowest cooking loss (15.86 %). Gumminess, chewiness and hardness of noodle containing 5 % MD encapsulated carrot powder were close to that of noodle containing no carrot powder. In conclusion, HP should be employed as the wall material for encapsulation of carrot juice that is to be incorporated in dried rice noodles.